Penerapan Model Scrum Pada Perancangan Aplikasi Penerimaan Siswa Baru MTS Nu 03 Suradadi - Diharja, Prawira; Rosmiati, Mia; Rahmayu, Mulia (LPPM Universitas Bina Sarana Informatika, 2025)
Digital transformation in the education sector demands innovation in service delivery, including the student admission process. This study presents an innovative approach through the application of the Scrum software development model to build a new student admission application at MTs NU 03 Suradadi. Unlike conventional methods, Scrum offers advantages in rapid iteration, adaptability to changing requirements, and close collaboration between the development team and stakeholders. The development process was carried out in stages through Scrum phases such as product backlog, sprint planning, development sprints, and sprint reviews and retrospectives. The result is a web-based application featuring key functionalities such as online registration, document uploads, registration proof printing, and user account management. The implementation results show a significant improvement in administrative efficiency and service accessibility, indicated by a 35% increase in student applicants, a reduction in data verification time from 3 days to 1 day, and a user satisfaction rate of 87%. These findings demonstrate that the application of Scrum not only improves product quality but also has a tangible impact in effectively and sustainably supporting the digitalization of educational services.